Malignancy associated changes in bronchial epithelial cells and clinical application as a biomarker - Ikeda, Norihiko; MacAulay, Calum; Lam, Stephen; LeRiche, Jean; Payne, Peter; Garner, David; Konaka, Chimori; Kato, Harubumi; Palcic, Branko (Lung cancer (Amsterdam, Netherlands), 1998)
A total of 74 bronchial brushing specimens, 24 from patients with advanced stage cancer, eight from patients with CIS, 31 from patients with atypical metaplasia and 11 from normal subjects were examined for the existence of malignancy associated changes (MAC). Conventional fiberoptic bronchoscopy and fluorescence endoscopy was carried out on every case. Each case was classified according to the highest grade of abnormality diagnosed by bronchial biopsy of the suspect areas. During the endoscopy examination, a bronchial brushing specimen was obtained from a visually normal area very remote from the abnormal area as possible such as the opposite lung or another lobe. The bronchial brushing specimens were fixed, mounted and stained by a DNA specific method and approximately 1500 images of individual nuclei per case were captured by an automated high resolution image cytometry. For each of these images, more than 100 nuclear features such as size, shape and chromatin spatial organization were calculated. Discriminant function analysis revealed nuclear features which differentiated between normal bronchial cell nuclei from the normal subjects and ostensively normal nuclei (MAC cell nuclei) from the lung cancer patients. The best discrimination was achieved when the frequency of individual cells expressing MAC was 50% or greater. With this threshold, 75% of the patients with invasive cancer and CIS were correctly classified. Fifty percent of those with severe or moderate atypia and 35% with mild atypia were also MAC positive. The frequency of cells expressing MAC also increased as the degree of abnormality of the groups increased. MAC may be a useful criterium to determine biological behavior of the intra-epithelial (pre-invasive) neoplasia.